PROGRAM PENGENDALIAN RESISTENSI ANTIBIOTIK DI TENGAH PANDEMIK COVID-19 BAGI TENAGA KESEHATAN DI INDONESIA - Legis Ocktaviana Saputri; Metta Octora; Astri Ferdiana; Fahrin Andiwijaya; Nurmi Hasbi; Azhar Rafiq (Jurnal Abdi Insani, 2022)
Antimicrobial resistance causes increased mortality and economic burden due to prolonged hospitalization, more expensive and longer use of antimicrobials, also the occurrence of superinfection which is difficukt to treat. The incidence of bacterial resistance to antibiotics is mainly due to the uncontrolled use of antibiotics, irrational treatment, as well as the lack of knowledge and behavior of health workers, especially general practitioners, specialists, and pharmacists towards emerging resistance conditions, especially reserved antibiotic groups in the era of the COVID-19 pandemic. The aim of this activity is to add insight and refresh information regarding the antibiotic resistance control program, as well as describe the ideal management of antibiotic resistance control through collaborative efforts of the various parties involved. This activity is packaged in form of national webinar using online zoom meeting and broadcast live on the YouTube platform of Faculty of Medicine University of Mataram. The achievement of the objectives of this activity is seen through the results of feedback questionnaires and the post-test score. Of more than 2000 participants who filled out the registration form, 643 of them consistently participated in the activities until the end of the webinar. The results questionnaire showed that 80.6% of participants strongly agreed with the usefulness of the webinar topic for a health practitioner, 79.3% of participants strongly agreed that the good explanation of the expertise, and 78.1% of participants strongly agreed and were helped by the organizing committee. This activity was able to increase participant's understanding of antibiotic resistance control, seen from the average post-test score of 80.19 out of 100. This activity increased awareness that controlling antimicrobial resistance requires integrated, multidisciplinary, and intersectoral collaboration from related parties for its successful implementation.